COMMUNICATING WITH EMPATHY: ETHICAL PRACTICES IN SOCIAL MEDIA - Bernadus Wibowo Suliantoro; Abdul Wahab Syakhrani (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research explores the importance of communicating with empathy as an ethical practice on social media. In an increasingly globalised digital era, interactions on social media are often marked by conflict, misunderstanding and unethical behaviour. Through an empathic approach, users can better understand and appreciate others' perspectives and feelings, which in turn reduces potential tensions and enriches the quality of interactions. Empathic communication supports honesty, transparency and inclusiveness, and promotes a more welcoming and safe digital environment. This research shows that empathy not only improves interpersonal relationships but also contributes to the formation of a more solid and harmonious online community. Thus, implementing empathic communication on social media is a key step in achieving better digital ethics and creating more humanised and meaningful interactions.